(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
One of the most important issues in the oil industry is scale formation, which causes a decline in output or financial loss. Scale deposits may range in severity from minor to severe. If the scale deposit is allowed to persist, it reduces formation pores, lowers production, and finally blocks the wellbore, resulting in unplanned downtime. Increased deposition results in lower operating efficiency, posing a serious problem for the sector. To address the problem, a more effective management plan is required. Rather of allowing the scale to grow up and then taking corrective action, the scale prevention approach should be applied from the beginning. Descaling is also a costly technique from a financial standpoint. Methods that can limit or eliminate the scale deposition technique in the early phases should be applied so that it does not adhere to the production should indeed be implemented. The notion of scale creation must be investigated in order to prevent making poor corrective decisions that might jeopardize output. The study considers the establishment of scales and their implications for the oil sector.